Parent depressive symptoms and offspring executive functioning. Issue 2 (7th February 2019) - Craun, Elizabeth; Lachance, Kathryn; Williams, Catherine; Wong, Maria M.
ABSTRACT: Introduction : Previous research has found mixed results when assessing the association between a parent's history of depressive symptoms and a child's abilities on measures of executive functioning. The purpose of this study was to replicate and expand upon these findings by evaluating the influence of a parent's depressive symptoms on a young person's executive functioning. Method : As part of a larger study, 135 children (54.8% female, aged 8–12) and one biological parent completed diagnostic screening interviews. Children then completed a brief executive functioning battery. Symptoms endorsed under the past major depressive episode module of the MINI International Neuropsychiatric Interview was used to measure depressive symptoms of parents. Results : While controlling for parent alcohol status and age, gender, intelligence, and current depressive symptoms of the child, linear regression models revealed that the parent's depressive symptoms significantly predicted deficits in Letter–Number Sequencing [ b  = −0.15 (0.07), p  < .05] and Motor Speed [ b  = −0.17 (0.05), p  < .005] on the Delis–Kaplan Executive Function System (D-KEFS) Trails Test. Parent depressive symptoms had no relationship with inhibition on the D-KEFS Color–Word Interference Test [ b  = −0.04 (0.14), p  = .74] or the Verbal Working Memory subtest of the Stanford–Binet [ b  = 0.14 (0.12) p  = .43]. Greater depressive symptoms in parents were associated with fewer perseverative errors on the Wisconsin Card Sorting Task (WCST) [ b  = 0.73 (0.32), p  < .05]. Conclusion : In sum, a parent's depressive symptomatology was differentially associated with a young person's neurocognitive abilities. Clinical implications were discussed.